FRI0335 PROGNOSTIC IMPACT AND CLINICAL CHARACTERISTICS OF INTERSTITIAL PNEUMONIA WITH AUTOIMMUNE FEATURES IN A MULTIDISCIPLINARY SETTING. (June 2019) - Marasco, Emiliano; Meloni, Federica; Zanframundo, Giovanni; Valentini, Adele; Morandi, Valentina; Codullo, Veronica; Volpiano, Lorenzo; Carruba, Claudia La; Motta, Francesca; Montecucco, Carlomaurizio; Cavagna, Lorenzo
Abstract : Background: Interstitial Pneumonia with Autoimmune feature (IPAF) is a recently defined disease that includes Interstitial Lung Disease (ILD) patients with features of autoimmunity, not satisfying any of the established classification criteria for connective tissue diseases (CTD). Even if IPAF pateints share clinical and serological findings with CTD, we are unaware about the clinical evolution of IPAF pateints. Objectives: To define the characteristics and evolution of IPAF patients in a multidisciplinary setting. Methods: We selected patients with a diagnosis of IPAF referring to a multidisciplinary Rheumatology/Pneumology/Radiology team at our hospital. We excluded from the analysis patients positive for antisynthetase antibodies, as diagnosed with antisynthetase syndrome. Data were retrospectively collected from our hospital medical records. Results: We analyzed 25 patients (19 females, 76%, 6 males, 24%), with a median onset age of 67 years (interquartile range, IQR, 59-74) and a follow-up of 32 months (IQR 22-69). ANA test was positive in 23 (92%) cases (fig 1 ), whereas cytoplasmic positivity was observed in 17 (68%). Anti-ENA screen was positive in 9 patients (36%) (7 [28%] anti-Ro52 and 2 [8%] anti-RNP). One patient (4%) was positive for anti-PM-Scl, 1 (4%) for anti-Mi2 and 1 (4%) for anti-Ku antibodies. These 2 latter antibodies are not included in the serological domain of IPAF. Patients had mainly a Non Specific Interstitial Pneumonia (NSIP) pattern (19 [76%]; fibrosing in 7 [28%], and with concomitant organizing pneumonia (OP) in 3 [12%]). Three (12%) patients had Usual Interstitial Pneumonia-like and 3 (12%) an OP pattern. The majority of patients (15 [60%]) satisfied only the morphological and serological domains. Clinical domains satisfied were: arthritis (4 [16%]), Raynaud's phenomenon (5 [20%]), palmar telangiectasias (2 [8%]), mechanic's hands (1 [4%]) and hiker's feet (1 [4%]). We observed other findings not included in IPAF criteria but suggestive for CTDs, both clinical (inflammatory myopathy 3 [12%]; dry eye1 [4%]; sclerodactyly 1 [4%]), and instrumental (scleroderma pattern at naifold capillaroscopy 1 [4%]; dilated esophagus at barium X-rays 2 [8%]). Clinical spectrum time course was variable in 5 (20%) cases: 3 (12%) patients developed arthritis after ILD, and 2 (8%) developed ILD respectively after arthritis and inflammatory myopathy onset. Three (12%) patients were admitted to the Intensive Care Unit for Rapidly Progressive (RP) ILD and 2 died (respectively 2 months and 54 months after ILD onset), whereas the alive patient had 2 ICU admission for RP-ILD. Five (20%) patients, including the only 1 dismissed from ICU, needed home O2 therapy. Ongoing and previous therapies are reported in figure 2 . Conclusion: We showed that the prognosis of IPAF is highly variable, with patients experiencing RP ILD, other slow progressive worsening of respiratory functions and other a substantially stable disease. Furthermore, we showed other findings, laboratory, clinical and instrumental, that could help clinicians in a better identification and stratification of IPAF patients. As a matter of fact, at present, IPAF appears as a generic term including very different conditions that can be further differentiated according to clinical and serological data. References: [1] Fischer A, et al. Eur Respir J 2015 [2] Sciré CA, et al. Resp Med 2017 [3] Sambataro G, et al. Eur Resp Rev2018 [4] Cavagna L, et al. Eur Resp Rev2018 Disclosure of Interests: Emiliano Marasco: None declared, Federica Meloni: None declared, Giovanni Zanframundo: None declared, Adele Valentini: None declared, Valentina Morandi: None declared, Veronica Codullo: None declared, Lorenzo Volpiano: None declared, Claudia La Carruba: None declared, Francesca Motta: None declared, Carlomaurizio Montecucco Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Sanofi, Genzyme, Lilly, MSD, Pfizer, UCB, Lorenzo Cavagna: None declared